Komposisi dan Identifikasi Senyawa Metabolit Sekunder pada Rumput Laut Merah (Gelidium sp) dengan Metode Maserasi - Putri Salma; Edison Edison; Andarini Diharmi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
Seaweed is one of the main aquaculture commodities that has economic value and has anormous potential in Indonesian. However the use of seaweed, especially the Gelidium sp type, is still undertutilitized. This research aims to determine the chemical composition and secondary metabolite compounds contained in the red seaweed Gelidium sp. The method used was experimental with different solvents, namely metanol, ethyl acetate and n-hexane in the extraction process. The test parameter analysis carried out was proximate analysis and analysis of secondary metabolite compounds in the red seaweed Gelidium sp. The results of the research were that in the proximate analysis, the water content was 14.42% in the wet weight, the ash content was 8.94% in the dry weight, The fat content was 1.25% in the drg weight and the carbohydrate content was 58.12%. The high carbohydrate content in seaweed is related to the presence of crude fiber components contained. Analysis of secondary metabolite compounds showed the presence of alkaloids, steroids, saponins and phenolics in the methanol solvent; alkaloid and steroid content in ethyl acetate; and alkaloids and steroids in n-hexane solvent. Secondary metabolite compounds in red seaweed Gelidium sp. It can be used as an antioxidant, antibacterial or medicine in the health sector